Early-strength filling material containing superfine tail mud

By combining ultrafine tailing sludge with blast furnace water quenching slag, converter steel slag and power plant desulfurization by-products, paste-shaped gelling materials are prepared, which solves the problem of difficult use of ultrafine tailing sand in mines and improves the early strength of the filling body and The peak rate has achieved solid waste resource utilization and environmental protection.

CN119118581APending Publication Date: 2024-12-13CHINA ENFI ENG CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271781.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Ultrafine tailings sand and tailings mud generated in mining are difficult to effectively utilize, resulting in safety hazards, environmental pollution and waste of resources. Traditional filling systems are difficult to meet the strength and peaking requirements under high mining indicators.

Method used

A filling material containing early-strength ultrafine tail sludge is used to combine the ultrafine tail sludge with blast furnace water quenching sludge, converter steel sludge and power plant desulfurization by-products, and add appropriate amount of admixtures to prepare paste-shaped gelling materials. Improve the early strength and convection rate of the filling body, and realize the resource utilization of solid waste.

Benefits of technology

It significantly improves the utilization rate of ultra-fine tail mud, enhances the early strength of the filling body, reduces raw material costs, solves the problems of low mining site topped rate and tailings storage, and promotes the coordinated utilization of multiple solid waste and environmental protection. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038927570000041
    Figure BDA0005038927570000041
  • Figure BDA0005038927570000071
    Figure BDA0005038927570000071
  • Figure BDA0005038927570000081
    Figure BDA0005038927570000081
Patent Text Reader

Abstract

The invention discloses an early strength type filling material containing superfine tail mud. The filling material comprises the superfine tail mud and a gel material, wherein the weight ratio of the superfine tail mud to the gel material is (3.5-5): 1; the gel material comprises the following components in parts by weight: 45-55 parts of blast furnace water-quenched slag; 30-40 parts of converter steel slag; 5-15 parts of a desulfurization by-product; 1-3 parts of an additive; the admixture is prepared from the following components in parts by weight: 12 to 23 parts of tricalcium silicate, 24 to 28 parts of calcium silicate, 11 to 27 parts of tricalcium aluminate, 3 to 12 parts of tetra calcium aluminoferrite, 5 to 15 parts of silica fume, 3 to 8 parts of dodecacalcium heptaaluminate, 3 to 8 parts of methyl polycarboxylic acid, 3 to 12 parts of vinyl acetate and 3 to 10 parts of calcium chloride. According to the method, the utilization rate of the superfine tail mud is fully increased, meanwhile, the early strength of a filling body is larger than or equal to 1 MPa in one day, and the problems of superfine tail mud stockpiling and filling mining are reasonably solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementitious materials, in particular to an early-strength filling material containing ultra-fine tailing mud. Background Art

[0002] A large amount of ultrafine tailings are produced and stored on the ground during mining production, causing safety hazards and ecological environmental problems. Backfilling mining technology backfills waste such as tailings into the goaf, which plays an increasingly important role in improving resource recovery rate, protecting the environment, and ensuring the safety of mining. The application of backfilling mining methods is also becoming more and more extensive. However, with the decline in the grade of ore produced by mining, in order to ensure the mineral processing index, the grinding particle size of the ore gradually decreases, resulting in the tailings particle size of the beneficiation plant becoming finer and finer, which brings new changes and requirements to the concentration, preparation, transportation and filling body strength formation related to the backfilling system. In addition, the mineral components of these ultrafine tailings sand and tailings mud are complex, the utilization value is low and the utilization is difficult. Due to environmental protection and other requirements, it is increasingly difficult for mining companies to occupy the spoil dump, and the number of tailings ponds in use is decreasing year by year. How to reasonably use ultrafine tailings sand and tailings mud is a difficult problem in waste recycling. Through the paste technology, ultra-fine tailings, blast furnace water-quenched slag, converter slag and power plant desulfurization by-products are synergistically disposed to realize the utilization of solid waste resources, which not only effectively solves the safety and pollution problems of tailings ponds, but also adds a small amount of admixtures suitable for solid waste-based cementitious materials, which can effectively improve the early strength and top connection rate of the filling body underground and control the movement of rock formations. At the same time, the return water before the plant realizes the recycling of water resources, thereby reducing the waste of water resources. Summary of the invention

[0003] The object of the present invention is to provide an early-strength filling material containing ultra-fine tailings, so as to realize the effective utilization of ultra-fine tailings.

[0004] The above purpose can be achieved by implementing the following technical solutions:

[0005] An early-strength filling material containing ultra-fine tailings, comprising ultra-fine tailings and gel material;

[0006] The weight ratio of ultrafine tail mud to gel material is 3.5-5:1;

[0007] The gel material comprises, by weight:

[0008] 45-55 parts of blast furnace water-quenched slag;

[0009] 30-40 parts of converter slag;

[0010] 5 to 15 parts of desulfurization byproducts;

[0011] 1 to 3 parts of admixture;

[0012] The admixtures are calculated by weight and include 12-23 parts of tricalcium silicate, 24-28 parts of calcium silicate, 11-27 parts of tricalcium aluminate, 3-12 parts of tetracalcium aluminoferrite, 5-15 parts of silica fume, 3-8 parts of dodecalyx heptaaluminate, 3-8 parts of methyl polycarboxylic acid, 3-12 parts of vinyl acetate and 3-10 parts of calcium chloride.

[0013] Optionally, the admixture includes, by weight: 17 parts of tricalcium silicate, 26 parts of calcium silicate, 19 parts of tricalcium aluminate, 8 parts of tetracalcium aluminoferrite, 10 parts of silica fume, 5 parts of dodecalyx heptaaluminate, 6 parts of methyl polycarboxylic acid, 7 parts of vinyl acetate, and 7 parts of calcium chloride.

[0014] Optionally, the cementitious material includes, by weight: 35 parts of converter slag powder, 50 parts of blast furnace water-quenched slag powder, 12 parts of desulfurization by-products, and 3 parts of admixtures.

[0015] Optionally, the ultrafine tailings mud comprises the following components in parts by weight: 28-39 parts of SiO2, 3-22 parts of CaO, 2-17 parts of Al2O3, 3-14 parts of MgO, 2-20 parts of Fe2O3, and 0-3 parts of P2O5.

[0016] Optionally, the converter slag comprises the following components in parts by weight: 3-20 parts of SiO2, 1-6 parts of MgO, 1-5 parts of Al2O3, 22-55 parts of CaO2, 12-26 parts of Fe2O3, 0-2 parts of P2O5, and 0-2 parts of MnO.

[0017] Optionally, the blast furnace water-quenched slag comprises the following components in parts by weight: by weight, 36-50 parts of CaO, 25-40 parts of SiO2, 8-18 parts of Al2O3, 3-10 parts of MgO, 0-3 parts of SO3, and 0-1 parts of Fe2O3.

[0018] Optionally, the desulfurization by-product includes the following components in parts by weight: by weight, 25-55 parts of CaO, 1-12 parts of SiO2, 1-7 parts of Al2O3, 0-6 parts of MgO, 28-50 parts of SO3, and 0-2 parts of Cl.

[0019] Optionally, the specific surface area of ​​the blast furnace water-quenched slag is 490m 2 / kg or more;

[0020] The specific surface area of ​​the desulfurized byproduct is 390 m 2 / kg or more;

[0021] The specific surface area of ​​the converter slag is 450m 2 / kg or more.

[0022] Optionally, the particle size distribution of the ultrafine tailing mud is D10 of 2.54-2.58 μm, D50 of 15.8-19.8 μm, and D90 of 102-122 μm.

[0023] Optionally, the content of particles with a particle size of less than 20 μm in the ultra-fine tailings is greater than 45 wt%.

[0024] The blast furnace water-quenched slag of the present invention has a 28d activity index of not less than 95%.

[0025] The converter slag of the present invention mainly comprises chernozemite (Ca2Fe2O5) and dicalcium silicate (C2S), has a high content of active components, and can fully stimulate the activity of blast furnace water-quenched slag.

[0026] The ultrafine tailings described in the present invention refer to tailings produced by a mining plant during mining production, and are not limited to their source or type.

[0027] The main component of the desulfurization by-product described in the present invention is similar to natural gypsum, that is, calcium sulfate dihydrate CaSO4·2H2O.

[0028] The blast furnace water-quenched slag, converter steel slag, desulfurization by-products and ultra-fine tailings used in the present invention can be purchased from the market or made at home, as long as the chemical composition requirements are met.

[0029] The chemical composition of the ultrafine tailings, converter slag, blast furnace slag, power plant desulfurization byproducts and admixtures described in the present invention refers to the content of various metals or mineral elements in oxides, and does not refer to the content of compounds existing in the ultrafine tailings, blast furnace slag or desulfurization byproduct blast furnace slag as oxides. In addition, the above chemical composition results can be obtained by conventional detection methods available in the art, such as typical fluorescence detection methods after or before burnout.

[0030] The technical solution of the invention has the following advantages:

[0031] The paste-type filling material of the present invention utilizes ultrafine tailings as aggregate, and replaces traditional paste cement with blast furnace water-quenched slag, etc., utilizes converter steel slag and desulfurization byproducts to synergize and preliminarily stimulate the activity of blast furnace water-quenched slag, and enhances the stimulation effect with an admixture to prepare a full solid waste cementitious material filling material, so that the ultrafine tailings are utilized as resources to the maximum extent, and significantly provides a better dosage of ultrafine tailings as aggregate in the full solid waste cementitious system, improves the strength, and can solve the problem of industrial solid waste (ultrafine tailings, steel slag and coal-fired power solid waste) reduction, harmlessness and resource utilization, promotes the coordinated utilization of multiple solid wastes and environmental protection, and provides a filling material in combination with paste filling mining technology to solve the problem of low top connection rate of the mine and tailings storage, laying the foundation for engineering application. The raw materials used have good safety. In addition, the preparation of early-strength paste filling materials with ultrafine tailings can solve the problem of low top connection rate of the mine and mining.

[0032] Compared with the existing paste filling materials, the aggregate particle size in the present invention is small, the slurry concentration is high, the utilization rate of ultrafine tailings is fully improved, and the early strength of the filling body (1 day ≥ 1MPa) reasonably solves the problem of ultrafine tailings storage and filling mining. Compared with the existing cementitious materials containing steel slag and blast furnace water-quenched slag, the cementitious material of the present invention has a simple composition, and the early strength increases significantly after adding admixtures. It is composed of three solid waste components: blast furnace water-quenched slag, converter steel slag and power plant desulfurization by-products, which greatly reduces the cost of raw materials. While the composition is simplified, due to the synergistic effect, it can still show good paste performance and rheological properties, including compressive strength and fluidity. The mortar ratio is 1:3.5-1:5. According to GB17671-1999 "Test Method for Cement Mortar Strength", the filling material of the present invention is prepared into a filling test block with a size of 70mm×70mm×70mm. The test block is cured at a temperature of 20°C and a humidity of more than 99.5%, showing good compressive strength. DETAILED DESCRIPTION

[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] The chemical compositions of the ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products used in the examples are shown in Table 1. The detection method is: X-ray fluorescence spectrometry (XRF), using an XRF-1800 X-ray fluorescence spectrometer to measure secondary X-rays for material composition analysis.

[0038] Table 1 Chemical composition of raw materials % analysis

[0039]

[0040] The particle sizes of the ultrafine tailings used in the examples are D10 of 2.56 μm, D50 of 17.8 μm, and D90 of 112 μm.

[0041] Example 1

[0042] The present embodiment provides a method for preparing a test block filled with ultra-fine tailings mortar, which is mainly composed of the following components in percentage by mass: the cementitious material comprises 35% of converter slag powder, 50% of blast furnace water-quenched slag powder, 14% of desulfurization by-products, 1% of an admixture (the admixture includes 17 parts of tricalcium silicate, 26 parts of calcium silicate, 19 parts of tricalcium aluminate, 8 parts of tetracalcium aluminoferrite, 10 parts of silica ash, 5 parts of dodecaluminate heptaaluminate, 6 parts of methyl polycarboxylic acid, 7 parts of vinyl acetate, and 7 parts of calcium chloride), the mortar-sand ratio is 1:4, and the slurry concentration is 78%.

[0043] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products are shown in Table 1.

[0044] The raw materials were weighed according to the ratio described in Example 1. The desulfurization by-products were ground to a specific gravity of 390 m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg, prepare the filling material sample according to GB17671-1999 "Test Method for Cement Mortar Strength", the sample size is 70mm×70mm×70mm, and maintain at a temperature of 20℃ and a humidity of more than 99.5%.

[0045] After casting and forming, the compressive strength was tested at different ages by curing. The test method was the same as that of comparative example 1. The test results are shown in Table 2.

[0046] Example 2

[0047] The present embodiment provides a method for preparing a test block filled with ultra-fine tailings mortar, which is mainly composed of the following components in percentage by mass: the cementitious material comprises 35% of converter slag powder, 50% of blast furnace water-quenched slag powder, 14% of desulfurization by-products, 2% of admixture (the admixture includes 12 parts of tricalcium silicate, 28 parts of calcium silicate, 11 parts of tricalcium aluminate, 12 parts of tetracalcium aluminoferrite, 5 parts of silica ash, 8 parts of dodecaluminate heptaaluminate, 3 parts of methyl polycarboxylic acid, 12 parts of vinyl acetate, and 3 parts of calcium chloride), the mortar-sand ratio is 1:3.5, and the slurry concentration is 78%.

[0048] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products are shown in Table 1.

[0049] The raw materials were weighed according to the ratio described in Example 2. The desulfurization by-products were ground to a specific gravity of 390 m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg, prepare the filling material sample according to GB17671-1999 "Test Method for Cement Mortar Strength", the sample size is 70mm×70mm×70mm, and maintain at a temperature of 20℃ and a humidity of more than 99.5%.

[0050] After casting and forming, the compressive strength was tested at different ages by curing. The test method was the same as that of comparative example 1. The test results are shown in Table 2.

[0051] Example 3

[0052] The present embodiment provides a method for preparing a test block filled with ultra-fine tailings mortar, which is mainly composed of the following components in percentage by mass: the cementitious material comprises 35% converter slag powder, 50% blast furnace water-quenched slag powder, 13% desulfurization by-product, 2% admixture (the admixture includes 23 parts of tricalcium silicate, 24 parts of calcium silicate, 27 parts of tricalcium aluminate, 3 parts of tetracalcium aluminoferrite, 15 parts of silica ash, 3 parts of dodecaluminate heptaaluminate, 8 parts of methyl polycarboxylic acid, 3 parts of vinyl acetate, and 10 parts of calcium chloride), the mortar-sand ratio is 1:5, and the slurry concentration is 80%.

[0053] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products are shown in Table 1.

[0054] The raw materials were weighed according to the ratio described in Example 3. The desulfurization by-products were ground to a specific gravity of 390 m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg, prepare the filling material sample according to GB17671-1999 "Test Method for Cement Mortar Strength", the sample size is 70mm×70mm×70mm, and maintain at a temperature of 20℃ and a humidity of more than 99.5%.

[0055] After casting and forming, the compressive strength was tested at different ages by curing. The test method was the same as that of comparative example 1. The test results are shown in Table 2.

[0056] Example 4

[0057] The present embodiment provides a method for preparing a test block filled with ultra-fine tailings mortar, which is mainly composed of the following components in percentage by mass: the cementitious material comprises 35% of converter slag powder, 50% of blast furnace water-quenched slag powder, 12% of desulfurization by-products, 3% of admixture (the admixture includes 17 parts of tricalcium silicate, 26 parts of calcium silicate, 19 parts of tricalcium aluminate, 8 parts of tetracalcium aluminoferrite, 10 parts of silica ash, 5 parts of dodecaluminate heptaaluminate, 6 parts of methyl polycarboxylic acid, 7 parts of vinyl acetate, and 7 parts of calcium chloride), the mortar-sand ratio is 1:4, and the slurry concentration is 82%.

[0058] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and desulfurization by-products are shown in Table 1.

[0059] The raw materials were weighed according to the ratio described in Example 4. The desulfurization by-products were ground to a specific gravity of 390 m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg, prepare the filling material sample according to GB17671-1999 "Test Method for Cement Mortar Strength", the sample size is 70mm×70mm×70mm, and maintain at a temperature of 20℃ and a humidity of more than 99.5%.

[0060] After casting and forming, the compressive strength was tested at different ages by curing. The test method was the same as that of comparative example 1. The test results are shown in Table 2.

[0061] Comparative Example 1

[0062] A paste filling material containing ultrafine tailings is mainly composed of the following components in percentage by mass: the cementitious material contains 50% blast furnace water-quenched slag powder, 35% steel slag, 15% desulfurization by-product, the mortar-sand ratio is 1:4, and the concentration of the paste filling material is 78% to 82wt%.

[0063] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products are shown in Table 1.

[0064] After casting and curing at different ages, compressive strength tests are carried out. The test method is:

[0065] Weigh the raw materials according to the above ratios. The desulfurization by-products need to be ground to a specific gravity of 390m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg. Mortar ratio 1:3.5-1:5, concentration 78%-82wt%. Prepare filling material sample according to GB17671-1999 "Test method for cement mortar strength", sample size 70mm×70mm×70mm, and maintain at 20℃ and humidity above 99.5%.

[0066] Comparative Example 2

[0067] A paste filling material containing ultrafine tailings is mainly composed of the following components in percentage by mass: the cementitious material contains 80% blast furnace water-quenched slag powder, 5% steel slag, 14% desulfurization by-products, 1% admixture (the admixture components are the same as those in Example 1), the mortar-sand ratio is 1:4, and the concentration of the paste filling material is 78% to 82wt%.

[0068] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products are shown in Table 1.

[0069] After casting and curing at different ages, compressive strength tests are carried out. The test method is:

[0070] Weigh the raw materials according to the above ratios. The desulfurization by-products need to be ground to a specific gravity of 390m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg. Mortar ratio 1:3.5-1:5, concentration 78%-82wt%. Prepare filling material sample according to GB17671-1999 "Test method for cement mortar strength", sample size 70mm×70mm×70mm, and maintain at 20℃ and humidity above 99.5%.

[0071] Comparative Example 3

[0072] A paste filling material containing ultrafine tailings is mainly composed of the following components in percentage by mass: the cementitious material includes 50% blast furnace water-quenched slag powder, 45% steel slag, 4% desulfurization by-products, 1% admixture (the admixture components are the same as those in Example 1), the mortar-sand ratio is 1:4, and the concentration of the paste filling material is 78% to 82wt%.

[0073] Among them, the chemical compositions of ultrafine tailings, blast furnace water-quenched slag powder, converter slag and power plant desulfurization by-products are shown in Table 1.

[0074] After casting and curing at different ages, compressive strength tests are carried out. The test method is:

[0075] Weigh the raw materials according to the above ratios. The desulfurization by-products need to be ground to a specific gravity of 390m 2 / kg, the mineral powder needs to be ground to a specific gravity of 490m 2 / kg, steel slag needs to be ground to a specific gravity of 450m 2 / kg. Mortar ratio 1:3.5-1:5, concentration 78%-82wt%. Prepare filling material sample according to GB17671-1999 "Test method for cement mortar strength", sample size 70mm×70mm×70mm, and maintain at 20℃ and humidity above 99.5%.

[0076] The test results are shown in Table 2.

[0077] Table 2 Compressive strength of mortar test blocks

[0078]

[0079]

[0080] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An early-strength filling material containing ultra-fine tail mud, characterized in that: Includes ultra-fine tail mud and gel materials; The weight ratio of ultrafine tail mud to gel material is 3.5-5:1; The gel material comprises, by weight: 45-55 parts of blast furnace water-quenched slag; 30-40 parts of converter slag; 5 to 15 parts of desulfurization by-products; 1 to 3 parts of admixture; The admixture comprises, by weight, 12-23 parts of tricalcium silicate, 24-28 parts of calcium silicate, 11-27 parts of tricalcium aluminate, 3-12 parts of tetracalcium aluminoferrite, 5-15 parts of silica fume, 3-8 parts of dodecaluminate heptaaluminate, 3-8 parts of methyl polycarboxylic acid, 3-12 parts of vinyl acetate, and 3-10 parts of calcium chloride.

2. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The admixture comprises, by weight, 17 parts of tricalcium silicate, 26 parts of calcium silicate, 19 parts of tricalcium aluminate, 8 parts of tetracalcium aluminoferrite, 10 parts of silica fume, 5 parts of dodecacalcium heptaaluminate, 6 parts of methyl polycarboxylic acid, 7 parts of vinyl acetate, and 7 parts of calcium chloride.

3. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The gelling material comprises, by weight, 35 parts of converter steel slag powder, 50 parts of blast furnace water-quenched slag powder, 12 parts of desulfurization by-products, and 3 parts of admixtures.

4. The early-strength filling material containing ultrafine tail mud according to claim 1, characterized in that: The ultrafine tailings mud comprises the following components in parts by weight: 28-39 parts of SiO2, 3-22 parts of CaO, 2-17 parts of Al2O3, 3-14 parts of MgO, 2-20 parts of Fe2O3, and 0-3 parts of P2O5.

5. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The converter slag comprises the following components in parts by weight: 3-20 parts of SiO2, 1-6 parts of MgO, 1-5 parts of Al2O3, 22-55 parts of CaO, 12-26 parts of Fe2O3, 50-2 parts of P2O, and 0-2 parts of MnO.

6. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The blast furnace water-quenched slag comprises the following components in parts by weight: 36-50 parts of CaO, 25-40 parts of SiO2, 8-18 parts of Al2O3, 3-10 parts of MgO, 0-3 parts of SO3, and 0-1 part of Fe2O3.

7. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The desulfurization by-product includes the following components in parts by weight: 25-55 parts of CaO, 1-12 parts of SiO2, 1-7 parts of Al2O3, 0-6 parts of MgO, 28-50 parts of SO3, and 0-2 parts of Cl.

8. The early-strength filling material containing ultrafine tail mud according to claim 1, characterized in that: The specific surface area of ​​the blast furnace water-quenched slag is 490m 2 / kg or more; The specific surface area of ​​the desulfurized by-product is 390m 2 / kg or more; The specific surface area of ​​the converter slag is 450m 2 / kg or more.

9. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The particle size distribution of the ultrafine tailings is as follows: D10 is 2.54-2.58 μm, D50 is 15.8-19.8 μm, and D90 is 102-122 μm.

10. The early-strength filling material containing ultra-fine tail mud according to claim 1, characterized in that: The content of particles with a particle size of less than 20 μm in the ultra-fine tail mud accounts for more than 45 wt%.